Maternal COVID-19 vaccine acceptance among Malaysian pregnant women: A multicenter cross-sectional study - Kalok, Aida; Razak Dali, Wira; Sharip, Shalisah; Abdullah, Bahiyah; Kamarudin, Maherah; Dasrilsyah, Rima Anggrena; Abdul Rahman, Rahana; Kamisan Atan, Ixora (Frontiers in Public Health, 2023)
Detection of the novel SARS-CoV-2 virus led to a global pandemic that resulted in devastating health, economic and social disruption. Pregnant mothers are susceptible to severe COVID-19 complications due to physiological and immunity changes in pregnancy. We aimed to assess the maternal vaccine acceptance of the COVID-19 vaccine. A multi-center study across four teaching hospitals in the Klang Valley, Malaysia was conducted between September 2021 and May 2022, involving women who received obstetric care at the institutions. A survey was conducted using an electronic questionnaire that contained demographics and clinical data, including the SARS-CoV-2 vaccine uptake and past infection. The other survey instruments were; 1) Maternal perceptions of COVID-19 vaccination, 2) COVID-19 pregnancy-related anxiety, and 3) Generalised anxiety disorder. The response rate was 96.6%, with a final number for analysis of 1272. The majority of our women were Malays (89.5%), with a mean age (SD) of 32.2 (4.6). Over four-fifths of our respondents received tertiary education and were in employment. Approximately a quarter of our women or their partners were healthcare workers. The maternal vaccine acceptance in our study was 77.1%. Tertiary education (p=0.046), employment status (p<0.001), household income (p<0.001), and health sector employment (p=0.001) were independent predictors of maternal willingness to be vaccinated. COVID-19 infection to self or among social contact and greater COVID-19 pregnancy-related anxiety are associated with increased odds of accepting the SARS-CoV-2 vaccine. Women who rely on the internet and social media as a source of vaccine information were one and a half times more likely to be receptive to vaccination (AOR 1.55; 95% CI 0.09 – 2.19). Strong correlations were observed between maternal vaccine acceptance and the positive perception of 1) vaccine information (p<0.001), 2) protective effects of vaccine (p<0.001), and 3) getting vaccinated as a societal responsibility (p<0.001). In conclusion, the high maternal vaccine acceptance rate among urban pregnant women in Malaysia is most likely related to their high socio-economic status. Responsible use of the internet and social media, alongside appropriate counseling by health professionals, is essential in reducing vaccine hesitancy among pregnant women.